PENGARUH KEPEMIMPINAN TERHADAP KINERJA PEGAWAI PADA DINAS PERUMAHAN DAN KAWASAN PERMUKIMAN KABUPATEN KEPULAUAN MENTAWAI - Lisa Rosita; Siti Osa Kosassy; Yenni Jufri (Jurnal Public Administration, Business and Rural Develoment Planning, 2023)
The method used in this research is quantitative using a survey method, namely research that takes a sample from one population and uses a questionnaire as the main data collection tool. 1). From the existing problems, the following conclusions can be drawn: Leadership at the Department of Housing and Settlements in the Mentawai Islands Regency is still not optimal, because the leader's ability to analyze problems is low, this can be seen from every report of problems faced by employees who still do not find solutions / bright spots from superiors, lack of courage and firmness of leadership in applying sanctions for violators of the personnel code of ethics so that there are still employees who come and go home not on time, delayed work completion, discommunication at work and lack of interest from the leadership in listening to every employee's complaint. 2.) The performance of employees at the Department of Housing and Residential Areas of the Mentawai Islands Regency is still not optimal, this can be seen from the quality of employee work, there are still errors in work, the quantity of work that is not in line with expectations, work that is not completed on time and still found employees who are not in the work room during working hours 3). Through the regression test Y = a + bX obtained 11.134 + 538 (Leadership Level), this indicates a positive influence generated by leadership on performance. This means that if leadership (X) is increased by 1 point, it will have an effect on performance of 11.134+538. Through the correlation test, the rXY value is 0.647. This means that there is a strong relationship between leadership and performance (Correlation Coefficient Interpretation between 0.60–0.799). The value of the Determinant Coefficient (R-Square) of leadership (X) is 0.418 or 41.8%. Thus the variation of increase and decrease in performance (Y) can be explained by the variable of leadership influence of 41.8%, while the remaining 58.2% of performance is influenced by other factors that are not included in the variables studied. The tcount is 6,112 while the ttable is 2,000. Thus tcount 6..112 > ttable 2,000 so that (Ho) is rejected and (Ha) is accepted, meaning that there is an influence between leadership and performance.